2014
DOI: 10.2147/vhrm.s61510
|View full text |Cite
|
Sign up to set email alerts
|

Blood and urine levels of heavy metal pollutants in female and male patients with coronary artery disease

Abstract: BackgroundHeavy metal pollutants such as cadmium (Cd), lead (Pb), and mercury (Hg) are rarely the subjects of cardiovascular research although they have been suspected for decades to negatively impact the circulatory system.MethodsApart from detailed anamnestic data, urinary levels of Cd and full blood levels of Pb and Hg were measured in 53 female (mean age: 68.04±7.03 years) and 111 male (mean age: 60.68±11.43 years) nonsmoking or never-smoking patients with angiographically verified and precisely quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…Chronic MeHg exposure is associated with cardiovascular disease (CVD) and cholesterol profiles [ 11 ]. It has been reported that Hg increases the risk of hypertension, carotid atherosclerosis, and myocardial infarction [ 12 - 15 ]. It has also been reported that the Hg level in the body is significantly associated with increases in serum ferritin, systolic blood pressure, diastolic blood pressure, total cholesterol, triglyceride, and waist to hip ratio [ 16 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic MeHg exposure is associated with cardiovascular disease (CVD) and cholesterol profiles [ 11 ]. It has been reported that Hg increases the risk of hypertension, carotid atherosclerosis, and myocardial infarction [ 12 - 15 ]. It has also been reported that the Hg level in the body is significantly associated with increases in serum ferritin, systolic blood pressure, diastolic blood pressure, total cholesterol, triglyceride, and waist to hip ratio [ 16 - 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…En arterosclerosis coronaria existen múltiples factores de riesgos considerados, entre los cuales se incluye la exposición a metales como el cadmio, el plomo y el mercurio; sin embargo, estos metales no han sido estudiados comúnmente en investigación cardiovascular [85], pero sí existen estudios en los que ya se han realizado algunas de estas mediciones. En ocasiones, el monitoreo de los niveles de metales es de gran utilidad cuando se requiere dar seguimiento a exposiciones ambientales en trabajadores del sector industrial, relacionándolos con algunos hábitos y su estilo de vida; los elementos evaluados suelen ser cadmio, cromo, manganeso, níquel y plomo en matrices biológicas como sangre, orina, vello axilar y saliva [63].…”
Section: Algunos Usos Y Aplicaciones De La Medición De Metalesunclassified
“…Experimental and epidemiologic evidence support that low-to-moderate chronic exposure to certain toxic metals plays a role in the development of cardiovascular disease, kidney disease, neurocognitive outcomes and also some cancers [ 1 , 2 , 3 , 4 , 5 ]. Cadmium has been associated with cardiovascular disease, chronic kidney disease, and some cancers [ 2 , 3 , 4 , 5 ]. Antimony and tungsten have been linked to cardiovascular disease, peripheral arterial disease, and diabetes [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%